1979
DOI: 10.1002/ana.410050602
|View full text |Cite
|
Sign up to set email alerts
|

Does a defect of energy metabolism in the nerve fiber underlie axonal degeneration in polyneuropathies?

Abstract: A number of chemically unrelated neurotoxic compounds and several types of metabolic abnormalities cause strikingly similar patterns of distal symmetrical polyneuropathy in humans and animals. Experimental studies with laboratory species have demonstrated that many toxic polyneuropathies are associated with distal and retrograde axonal degeneration occurring in vulnerable nerve fiber tracts in the central as well as the peripheral nervous system. This has been termed central-peripheral distal axonopathy. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(60 citation statements)
references
References 27 publications
1
59
0
Order By: Relevance
“…NF-containing distal axonal enlargements. Spencer et al (14) have suggested that six-carbon compounds and their derivatives impair enzymes of intermediary metabolism, causing a progressive failure of the energy supply needed for NF transport; hence, NF would stop and accumulate focally. According to Graham et al (28) 2,5-HxD reacts directly with 6-amino groups of lysine residues of NF proteins to form aromatic pyrrole derivatives; autooxidation of these pyrroles would lead to cross-link formation; the high stability and low turnover rate of axonal NF would make them especially vulnerable to this toxic effect; aggregates of NF, progressively cross-linked during their migration along the axon, would be transported at decreasing rates and eventually blocked at distal nodes of Ranvier.…”
Section: A3mentioning
confidence: 99%
See 1 more Smart Citation
“…NF-containing distal axonal enlargements. Spencer et al (14) have suggested that six-carbon compounds and their derivatives impair enzymes of intermediary metabolism, causing a progressive failure of the energy supply needed for NF transport; hence, NF would stop and accumulate focally. According to Graham et al (28) 2,5-HxD reacts directly with 6-amino groups of lysine residues of NF proteins to form aromatic pyrrole derivatives; autooxidation of these pyrroles would lead to cross-link formation; the high stability and low turnover rate of axonal NF would make them especially vulnerable to this toxic effect; aggregates of NF, progressively cross-linked during their migration along the axon, would be transported at decreasing rates and eventually blocked at distal nodes of Ranvier.…”
Section: A3mentioning
confidence: 99%
“…Two main hypotheses have been put forward, both assuming that NF are transported at decreasing rates and are eventually blocked (14,15). However, slow axonal transport has not been studied.…”
mentioning
confidence: 99%
“…Investigations on the axonal flow of labeled protein in hexacarbon neuropathy show that slow axonal transport is impaired with a secondary focal slowing of fast axonal transport (82). In acrylamide intoxication the slow transport components appear not to be affected, while there are local disturbances of the fast transport in distal parts of the axon.…”
Section: Axonal Transport and Distal Axonopathymentioning
confidence: 99%
“…Selected list of industrial toxic chemicals producing structural damage in the peripheral nervous system (32,45,83,84,86). 82). However it is not known whether the delay of axonal transport is the primary defect, as it develops at the same time as the appearance of the morphologicallesions in hexacarbon-induced neuropathy (44).…”
Section: Advances In the Understanding Of The Pathogenesis Cellular Tmentioning
confidence: 99%
“…Some have postulated that neurofilaments accumulate because of a defect in axonal transport, perhaps secondary to a defect in energy metabolism (14). Cavanagh and Bennetts have suggested that the defect may lie in the catabolism of neurofilaments (15).…”
Section: Introductionmentioning
confidence: 99%